EVALUATION OF BIOCHEMICAL COMPOSITION IN SOME PROMISING NON-QPM INBRED LINES AND QPM HYBRIDS OF QPM INBRED LINES AND QPM HYBRIDS OF MAIZE ( MAIZE (Zea mays Zea mays L.) - K.K. SONI,; J.M. PATEL,; R.A. GAMI,; S. B. GONDALIYA,; S.K. SHAH,; M.K. CHAUDHARY, (The Bioscan, 2019)
Present study was conducted to identify overall nutritionally superior/versatile genotypes through evaluation of biochemical constituents in nine genotypes of maize consecutively for three years. In biochemical analysis, significantly higher carbohydrate content was recorded from HQPM-1(70.65%), CM-140(68.78%) and VL- 109178(68.59%), the highest starch content was recorded from BLD-233(61.91%), HY-235(61.78%) and GAYMH-1(61.43%), the highest protein content was recorded from HY-235(10.26%), JCS-2-7(10.11%) and VL- 109178(10.11%), the highest oil content was recorded from HQPM-1(4.68%), GAYMH-1(4.99%) and JCS-2- 7(4.83%). Genotypes VL-109178 (3.85%), CM-140(3.47%) and CM-135(3.43%) recorded highest lysine content whereas JCS-2-7(0.6%), BLD-233(0.61%) and GAYMH-1(0.55%) recorded highest tryptophan content. Significant negative correlation was found between protein and lysine contents (p<0.01). Furthermore, non-significant differences (p>0.05) were observed among maize genotypes for fatty acid composition of oil and micronutrients. High levels of unsaturated fatty acids were recorded in QPM hybrids HQPM-1 (77.86%) and GAYMH-1 (83.09%) whereas BLD-233 (79.4%) and JCS-2-7(78.49%) recorded nearly similar amount of it. On the other end, HQPM-1 had the highest value of iron (49.00ppm) and zinc (37.5ppm) whereas VL-1010090 recorded the maximum Mg content (943.3ppm). Besides, based on varietal rating on the basis of all quality attributes, HQPM- 1, BLD-233 and JCS-2-7 were identified to be overall superior multipurpose genotypes in that order to be useful for maize nutritional improvement.